Definition of a strategy for re-opening the Garonne and Ariège rivers for downstream migration of salmon: simulation of fish mortality caused by hydroelectic installations during downstream migration - Bosc, Serge; Larinier, M. (HAL CCSD, 2000)
The main aim of this study was to design a model for evaluating the total losses of Atlantic salmon smolts caused by the various hydroelectric installations on the Garonne basin upstream of Toulouse, during downstream migration. The proposed model is a primitive phenomenological model representing the drop in level for each installation. It takes into account the hydrology of the water course during the migration period as well as the characteristics of the installation and the likelihood of death as the young salmon pass through the turbines. Given the distribution of potential salmon nursery habitat on the various water courses or sectors of water, the work made it possible to define stretches on which stocking actions should be concentrated. It also identified power stations for which it was necessary to install efficient fish-passes and stretches or sectors of water courses which could benefit from restoration or which on the contrary were not suitable or too difficult to restore. Le principal objectif de cette étude était de concevoir un modèle permettant d'apprécier les pertes cumulées lors du passage des juvéniles de saumon atlantique en dévalaison par les différents aménagements hydroélectriques équipant le bassin de la Garonne en amont de Toulouse. Le modèle proposé est un modèle phénoménologique rustique schématisant la dévalaison au niveau de chaque aménagement et prenant en compte l'hydrologie du cours d'eau en période de migration, les caractéristiques de l'aménagement et les probabilités de dommages lors du transit des juvéniles dans les turbines. Ce travail a permis, en regard de la distribution des potentialités sur les différents cours d'eau ou secteurs de cours d'eau, de définir les tronçons sur lesquels il convient de concentrer les actions d'alevinage, les centrales sur lesquelles l'installation d'aménagements efficaces pour la dévalaison est une nécessité, les axes ou secteurs sur lesquels la restauration paraît intéressante ou au contraire difficile, voire irréaliste.